2008
DOI: 10.1518/001872008x354156
|View full text |Cite
|
Sign up to set email alerts
|

On the Portability of Computer-Generated Presentations: The Effect of Text-Background Color Combinations on Text Legibility

Abstract: Some practical rules on combining TB colors are given to enhance the legibility of presentations, especially important for the legibility of projected texts.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
15
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(18 citation statements)
references
References 16 publications
3
15
0
Order By: Relevance
“…Our findings appear to give support to both researchers: Black/White and Blue/ White led to the best performance resulting in the fastest reading speed. These findings agreed with recent research by Greco et al (2008). However, our results contrast with those of Matthews et al (1989) and Pastoor (1990) in which they observed no effect of using red or blue stimuli.…”
Section: Text/background Color Combination Of E-booksupporting
confidence: 92%
“…Our findings appear to give support to both researchers: Black/White and Blue/ White led to the best performance resulting in the fastest reading speed. These findings agreed with recent research by Greco et al (2008). However, our results contrast with those of Matthews et al (1989) and Pastoor (1990) in which they observed no effect of using red or blue stimuli.…”
Section: Text/background Color Combination Of E-booksupporting
confidence: 92%
“…Moreover experimental results revealed that e-book displays with larger color differences of the text/ background, color-combinations resulted in higher subject reading performance and subjective preferences, which were similar to the conclusions of other studies (Wang et al, 2004;Ramadan and Mohamed, 2010). The ndings appear to give support to both researchers: Black/White and Blue/ White led to the best performance resulting in the fastest reading are supported by the recent research by Greco et al (2008). Almost the same pattern of differences was found in both reading speed and comprehension measures which show that overall the Black/White combination led to high performance compared to the other combinations.…”
Section: Text/background Color Combinationsupporting
confidence: 70%
“…In fact, contrast in brightness affects performance in various visual tasks and subjective evaluations concerning the legibility of texts and icons. Furthermore, legibility tightly correlates with pleasantness . Thus, contrast in lightness facilitates object recognition.…”
Section: Discussionmentioning
confidence: 99%